Self-rated Health and Housing among Indigenous Australians - Mintah, Kwabena; Churchill, Rejoice E A; Baako, Kingsley Tetteh; Kavaarpuo, Godwin (My University, 2022)
This study empirically examines the effects of self-reported health on housing tenure decisions of Indigenous Australians. Using longitudinal data drawn from the Household, Income and Labour Dynamics in Australia (HILDA) Survey covering 2001-2019, we use indicators of housing tenure decisions that reflect home ownership and transitions from renting to owning and vice versa. We find that better health is associated with a higher probability of homeownership and a higher probability of transitioning from renting to homeownership. We examine preference to continue living in an area, neighbourhood satisfaction, home satisfaction and social capital as potential channels through which health influence housing tenure decision. We find evidence to support the validity of all these factors as channels except social capital. The policy implications of the study are then explored.
Journal of Economics, Race, and Policy
Keywords: Health and wellbeing; Housing, communities and neighbourhoods